Isotopic signature and nano-texture of cesium-rich micro-particles: Release of uranium and fission products from the Fukushima Daiichi Nuclear Power Plant - Junpei Imoto (Nature Portfolio, 2017)
Abstract Highly radioactive cesium-rich microparticles (CsMPs) released from the Fukushima Daiichi Nuclear Power Plant (FDNPP) provide nano-scale chemical fingerprints of the 2011 tragedy. U, Cs, Ba, Rb, K, and Ca isotopic ratios were determined on three CsMPs (3.79–780 Bq) collected within ~10 km from the FDNPP to determine the CsMPs’ origin and mechanism of formation. Apart from crystalline Fe-pollucite, CsFeSi2O6 · nH2O, CsMPs are comprised mainly of Zn–Fe-oxide nanoparticles in a SiO2 glass matrix (up to ~30 wt% of Cs and ~1 wt% of U mainly associated with Zn–Fe-oxide). The 235U/238U values in two CsMPs: 0.030 (±0.005) and 0.029 (±0.003), are consistent with that of enriched nuclear fuel. The values are higher than the average burnup estimated by the ORIGEN code and lower than non-irradiated fuel, suggesting non-uniform volatilization of U from melted fuels with different levels of burnup, followed by sorption onto Zn–Fe-oxides. The nano-scale texture and isotopic analyses provide a partial record of the chemical reactions that occurred in the fuel during meltdown. Also, the CsMPs were an important medium of transport for the released radionuclides in a respirable form.